Textiles. Quantitative chemical analysis. Mixtures of chlorofibres, certain modacrylics, certain elastanes, acetates, triacetates with certain other fibres (method using cyclohexanone) Part 21, (29th January 2020) - British Standards Institution,
No abstract available